Marketing strategies in the function of competitiveness of companies in the Republic of Serbia - Milić Marko; Đervida Ružica; Vujičić Slađana (Trendovi u Poslovanju)
The development of a modern company implies the effective implementation of various marketing strategies. Marketing strategies are the basis for an effective marketing plan that is an integral part of the company's business plan. The marketing plan is defined and shaped in practice between the design of an adequate marketing strategy and the implementation of the marketing campaign. Defining marketing strategies implies a clear specification of a series of specific actions that need to be successfully implemented. Achieving defined marketing goals is directly correlated with well-defined marketing strategies. The key is to ensure measurable results when implementing a marketing strategy. Marketing strategies represent the foundation for developing a tactical plan in the company and thus have an extremely significant impact on the success of the company's operations. Therefore, there is a necessity to clearly define the types of marketing strategies that will be implemented in a certain company. In Republika Srpska, as an integral part of Bosnia and Herzegovina, one can identify different types of marketing strategies applied by companies in order to achieve their business goals. The specifics of the market influence the definition and application of specific marketing strategies. The choice of marketing strategy should always be in the function of improving the competitiveness of a particular company.